Jitsi meet integration analysis with moodle for synchronous distance learning - Kadek Virgan Ardiat; I Nyoman Buda Hartawan; Ni Wayan Suardiati Putri (Institute of Computer Science (IOCS), 2023)
After the Covid-19 pandemic, learning activities were used to being carried out online. Utilization of the Learning Management System is starting to be widely used for asynchronous learning, while synchronous learning is carried out using different applications. In this study, a video conferencing server design was created to integrate Jitsi Meet with Moodle. On the Moodle server, install and configure the NginX, MariaDB, php, Moodle packages and install the Jitsi Meet plugin on Moodle. On the Cacti server, install and configure Cacti, manufacture devices, create graph trees, add graphs and monitor data on graphs. Black Box Testing is carried out to test the Jitsi Meet feature and to monitor the average use of CPU and memory during meetings. The results of the Black Box test on the Jitsi Meet feature get a percentage of 89.7% completion. In testing the average CPU usage in the Cacti application, a percentage of 3.21 was obtained. In testing the average memory usage in the Cacti application, a percentage was obtained of 33.56%.